Penguatan Ekonomi Lokal melalui Produk Inovatif Perikanan: Abon Ikan dan Nugget Ikan - Guspiandra, Nori; Agustavira, Delvia; Nofirsa, Corry; Tuswanto, Amri Romadon; Zabel, Ryolando; Prayitno, Joko; Sitepu, Clarisa Natalie Br; Sidauruk, Santhy Wisuda (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
PKK empowerment program in Pambang Pesisir Village through training in the production of fish floss and nuggets. Using an interactive approach, 15 PKK women participated in a 3-hour hands-on demonstration. Activities included visual counseling (30 minutes), a Q&A session (15 minutes), a product-making demonstration (90 minutes), and independent practice (45 minutes). The results showed a significant increase in participants’ understanding and skills, measured through pre- and post-training questionnaires. The participant satisfaction rate reached 95%, with 80% of them interested in developing businesses based on the products learned. The program successfully introduced high-value fish processing alternatives, opening opportunities for income diversification in coastal communities.The training increased participants' awareness of the potential of local marine resources. Further analysis showed a 40% improvement in participants' knowledge of the nutritional value of processed fish products. Additionally, 70% of participants reported increased confidence in their entrepreneurial abilities. The program also strengthened collaboration among PKK members, with 60% expressing interest in forming joint business groups. The potential economic impact is estimated to increase household income by up to 25% in the medium term. Recommendations for program sustainability include establishing production cooperatives, advanced training in small business management, and developing local marketing networks. The study concludes that empowerment programs based on practical skills can serve as effective catalysts for the economic development of coastal communities.